Lesbianism as Portrayed in Clare Lydon’s This London Love - Miftach Khairani (JURNAL ILMIAH BAHASA DAN SASTRA, 2020)
Abstract This study entitled “Lesbianism as Portrayed in Clare Lydon’s This London Love.” This study explains about the causes and effects of lesbianism which found in the novel This London Love by Clare Lydon. The purpose of this study is to find out the causes of lesbianism experienced by the two main characters and effects of lesbianism experienced by the two main characters. This study uses Uzoeshi’s theory to analyze the causes and effects of lesbianism in a novel in line with Queer Theory. In analyzing this thesis, the writers use qualitative descriptive method that presents all data in the form of words and sentences and use library research as a way to collect data by reading and selecting quotations from the novel This London Love. From this research it is found that the two main characters in the novel experienced four causes of lesbianism which are inadequate parenting, associating with lesbians, heterophobic, and looking masculine; and two effects of lesbianism which are alcoholism and jealous reactions. So, hopefully this research is expected to be able to become a reference which can provide useful information child abuse and for people to prevent the act of child sexual abuse and help the victims. Keywords: Lesbianism, Queer Theory, Heterophobic, Looking Masculine, Alcoholism.